Association between lipid accumulation products and mortality outcomes in patients with osteoporosis and osteopenia - Yazhou Liu; Ying Yang; Yuhao Li; Wenbo Ding; Xiaodong Yang (Experimental Gerontology)
Background: Osteoporosis (OP) and osteopenia are metabolic bone disorders associated with increased fragility and fracture risk. While lipid accumulation products (LAP) are emerging as potential markers of metabolic health, their prognostic significance in patients with OP or osteopenia remains unclear. The objective of this study is to elucidate the relationship between lipid accumulation products (LAP) and all-cause as well as cardiovascular mortality in individuals diagnosed with either condition. Methods: Data from the 2007–2018 National Health and Nutrition Examination Survey (NHANES) were retrospectively analyzed. Kaplan-Meier survival curves, multivariable Cox proportional hazards regression, and restricted cubic spline plots were used to evaluate the association between LAP and mortality outcomes in patients with OP or osteopenia. Subgroup and threshold analyses were also conducted. Results: This study included 4959 patients diagnosed with OP or osteopenia, followed over a comprehensive duration of 12 years, during which 800 instances of all-cause mortality and 194 deaths attributed to cardiovascular diseases were documented. A linear negative correlation was identified between LAP and both all-cause and cardiovascular mortality among patients with OP or osteopenia. Notably, at an LAP level of 3.69, the risk ratio reached 1, indicating a transition in mortality risk from high to low. Subgroup analyses revealed a more pronounced association between LAP and mortality. Conclusion: Our study revealed a significant linear negative correlation between the lipid accumulation product (LAP) and both all-cause and cardiovascular mortality in patients diagnosed with osteoporosis (OP) and osteopenia.